2007
DOI: 10.1007/s00216-007-1767-0
|View full text |Cite
|
Sign up to set email alerts
|

Complementary molecular and elemental detection of speciated thioarsenicals using ESI-MS in combination with a xenon-based collision-cell ICP-MS with application to fortified NIST freeze-dried urine

Abstract: The simultaneous detection of arsenic and sulfur in thioarsenicals was achieved using xenon-based collision-cell inductively coupled plasma (ICP) mass spectrometry (MS) in combination with high-performance liquid chromatography. In an attempt to minimize the (16)O(16)O(+) interference at m/z 32, both sample introduction and collision-cell experimental parameters were optimized. Low flow rates (0.25 mL/min) and a high methanol concentration (8%) in the mobile phase produced a fourfold decrease in the m/z 32 bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Simultaneous analyses [33] of m/z 75( 75 As + ) and 32( 32 S + ) of thioarsenic compounds were performed as follows:…”
Section: Hplc-icp-ms and Hplc-tandem Ms Conditionsmentioning
confidence: 99%
“…Simultaneous analyses [33] of m/z 75( 75 As + ) and 32( 32 S + ) of thioarsenic compounds were performed as follows:…”
Section: Hplc-icp-ms and Hplc-tandem Ms Conditionsmentioning
confidence: 99%
“…The increasing popularity is typical for proteomics, including the identification and quantitation of pro teins using heteroatoms (phosphorus and sulfur), and metallomics-investigation of traces of metals in liv ing organisms [97][98][99][100]. The determination of sulfur [60,101,102], phosphorus [60,[103][104][105] and sele nium [106][107][108] at low levels using quadrupole ICP MS instrument becomes possible only by means of gas filled cells.…”
Section: Application Of Cellsmentioning
confidence: 99%
“…In the measurement of thioarsenicals in urine by HPLC-ICP-MS, the use of Xe as a collision gas gave a much improved LOD down to about 10 ng g À1 for S at m/z 32 than that obtained with He, presumably because of the greater efficiency with which 32 O 2 + was dissociated. 228 A study on the role of S in arsenic cycling found that the oxidation of As III was linked to the presence of S-oxidising bacteria and that the production of As V was greatly enhanced by the addition of sulfide or thiosulfate. 229 The rate and extent of these processes was linked to the concentration of bacteria and the reduced-S:As III ratio.…”
Section: Sulfurmentioning
confidence: 99%